Demography, a Fully Formed Science or a Science in the Making? An Outline Programme. - Courgeau, Daniel; Franck, Robert (Population (16342941), 2007)
A commentary on an article by Dominique Tabutin that appears in this issue. In his article, Tabutin asserted that demography today is undoubtedly a true science, with its body of research objects, methods, and paradigms. The writers examine this view, seeking to understand why Tabutin nevertheless goes on to state that demography remains hesitant when it comes to understanding and explaining. They explore the subject matter of demography, outline a more precise program for the discipline, investigate its paradigms, and highlight the utility of a more axiomatic approach that would bolster its scientific pertinence and thereby its reliability.